Purity Effect of High-Strength Steel on Failure Behavior of Automobile Front Axle - Huan Xue (Advances in Materials Science and Engineering, 2022)
As unpredictable fracture of the front axle will lead to serious safety accidents, its failure behavior study is essential. This paper analyzes typical cracks on I-shaped and leaf springs of the front axle made by Steel A and Steel B. Steel B has a lower content of S, N, Cu, and Sn than Steel A. In order to identify the failure mechanism difference, the low magnification etch test, and metallographic and scanning electron microscope analyses were conducted. The results show that the microstructures are tempered sorbite, and the cracks are with intergranular fracture characteristics. The aggregated distribution of sulfide inclusions in the matrix of Steel A is higher than that of Steel B. Copper-rich particles are detected in the cracks of Steel A. The result indicates that the purity distinction of raw steel can have a big difference on the cracking rate of the front axle even under the same manufacturing process. Relevant suggestions to reduce the cracking are put forward from the aspects of raw materials and process conditions.